How Can and Should We Reach and Train Our Future Pastors and Christian Leaders?. Issue 1 (April 2020) - Stetzer, Ed; MacDonald, Andrew
This article represents a plenary session address for the Asbury Seminary Faculty Retreat, September 20, 2019, by Ed Stetzer, the Billy Graham Chair of Church, Mission, and Evangelism at Wheaton College, Dean of the School of Mission, Ministry, and Leadership at Wheaton College, and Executive Director of the Billy Graham Center. The article addresses six significant trends facing theological education. Following this, three mission challenges are derived from the trends, followed by three implications moving forward.